The process of decision-making in the health care sector - Furtak, Marzena; Książek, Piotr; Warchoł-Sławińska, Ewa (Polish Journal of Public Health, 2011)
The process of decision-making is the simplest and the most effective mechanism of changing the surrounding reality, defi ning the target, and of givinge our life a new direction which we are going to follow. In the health care system, which is one of the most structurally and functionally complex systems decision-making is a diffi cult and important social choice as it influences the most essential human values: health and life. These conditions influence the fact that, in this particularly important sector of the economy, all decisions should be made with particular care and prudence. It determines the rationality of the process, which is always mentioned as one among other basic values of effi cient and eff ff ective operation.